Doxorubicin attached to HPMA copolymer via amide bond modifies the glycosylation pattern of EL4 cells - Kovar, Lubomir; Etrych, Tomas; Kabesova, Martina; Subr, Vladimir; Vetvicka, David; Hovorka, Ondrej; Strohalm, Jiri; Sklenar, Jan; Chytil, Petr; Ulbrich, Karel; Rihova, Blanka (Tumour biology, 2010)
To avoid the side effects of the anti-cancer drug doxorubicin (Dox), we conjugated this drug to a N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer backbone. Dox was conjugated via an amide bond (Dox-HPMA(AM), PK1) or a hydrazone pH-sensitive bond (Dox-HPMA(HYD)). In contrast to Dox and Dox-HPMA(HYD), Dox-HPMA(AM) accumulates within the cell's intracellular membranes, including those of the Golgi complex and endoplasmic reticulum, both involved in protein glycosylation. Flow cytometry was used to determine lectin binding and cell death, immunoblot to characterize the presence of CD7, CD43, CD44, and CD45, and high-performance anion exchange chromatography with pulsed amperometric detector analysis for characterization of plasma membrane saccharide composition. Incubation of EL4 cells with Dox-HPMA(AM) conjugate, in contrast to Dox or Dox-HPMA(HYD), increased the amounts of membrane surface-associated glycoproteins, as well as saccharide moieties recognized by peanut agglutinin, Erythrina cristagalli, or galectin-1 lectins. Only Dox-HPMA(AM) increased expression of the highly glycosylated membrane glycoprotein CD43, while expression of others (CD7, CD44, and CD45) was unaffected. The binding sites for galectin-1 are present on CD43 molecule. Furthermore, we present that EL4 treated with Dox-HPMA(AM) possesses increased sensitivity to galectin-1-induced apoptosis. In this study, we demonstrate that Dox-HPMA(AM) treatment changes glycosylation of the EL4 T cell lymphoma surface and sensitizes the cells to galectin-1-induced apoptosis.
Keywords: nosiče léků; Drug Carriers; nádorové buněčné linie; Doxorubicin; apoptóza; průtoková cytometrie; Endoplasmic Reticulum; endoplazmatické retikulum; Lymphoma, T-Cell; Golgiho aparát; Mice; Cell Proliferation; Cell Line, Tumor; glykosylace; Leukosialin; western blotting; Flow Cytometry; Blotting, Western; Glycosylation; doxorubicin; kyseliny polymethakrylové; zvířata; amidy; Antibiotics, Antineoplastic; myši; proliferace buněk; lymfom T-buněčný; Amides; protinádorová antibiotika; antigeny CD43; galektin 1; Galectin 1; Polymethacrylic Acids; Golgi Apparatus; Apoptosis; Animals